Saturday

April 19, 2014

April 19, 2014

Posted by **Krystal** on Monday, September 23, 2013 at 10:45pm.

- algebra 2 -
**Steve**, Tuesday, September 24, 2013 at 12:44amthe same way you solve any quadratic. The first is:

x = [-8±√(8^2-4(3)(-91))]/(2*3)

= (-8±√1156)/6

= (-8±34)/6

= -7,13/3

solve the other in like wise.

**Related Questions**

math - If the answer is 1-2/3m what is the question> How can you solve ...

algebra - multiply and simplify 10x^3 over 3r^3 multiplied by 9r^4 over 100x Is ...

Algebra - I am stumped by these two LCM questions for some reason. Find The LCM ...

algbra - i was wondering what did i do wrong in this 10. Divide (3x – 2)(x - 4...

Math - Solve the following system of equations. 8x + 5y = -91 3x + y = -21

Math - Solve the following system of equations. 8x + 5y = -91 3x + y = -21

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

Math - What are the solution sets of the following 3 problems,the square root of...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

Algebra II - Assume that no denomenator equals 0. (7x^2+3x-9)-(-x^2+8x-3) = 7x^2...